Determinants of public trust towards unit trust investment: a study using PLS-SEM / Zahariah Mohd Zain ...[et al.] - Mohd Zain, Zahariah; Ab. Halim, Roslilee; Abdul Rashid, Arlinah; Apat, Abdul Yazid; Hashim, Nurhazirah; Abdul Wahab, Abdul Azeez Oluwanisola (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, 2018)
There are many types of investment exist in our world. People can choose where to invest their money based on the risk that they are willing to take. There is investment with low risk, medium risk and high risk. Unit trust is classified as medium risk investment. This research will focus on the biggest company in Malaysia that offer unit trust investment to public which is Permodalan Nasional Berhad (PNB) and it wholly subsidiary company, Amanah Saham Nasional Berhad (ASNB). It will focus on finding the determinants to build a trust from public to inves t in unit trust. Company strong brand name, word of mouth and effective promotional strategies have been chosen as the independent variables. Primary data will be use in this research in the form of distributing questionnaires and the data will be analysed with the help of Statistical Package for Social Science (SPSS). The findings have shown that all three independent variables have an effect on the dependent variable namely public trust. Using the regression analysis, the most significant independent variable is company strong brand name.